Effects of SARS-CoV-2 Infection During Late Pregnancy on Early Childhood Development: A Prospective Cohort Study - Wu, Tianchen; Chen, Lian; Wang, Yuanyuan; Shi, Huifeng; Niu, Jieqiong; Yin, Xiaohan; Li, Mengshi; Tan, Chang; Jiang, Hai; Zheng, Danni; Wei, Yuan; Zhao, Yangyu; et al. (Frontiers in Pediatrics, 2021)
Abstract Background: There is little direct or indirect evidence of the effects of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection during pregnancy on early childhood development. Methods: We conducted a prospective, observational cohort study in China from May 1 to October 31, 2020, that enrolled 135 mother-infant dyads: 57 dyads in the infection cohort and 78 in the non-infection cohort. Among all infants, 14.0% of them was preterm birth in the infection cohort and 6.4% in the non-infection cohort. Participants were followed by telephone interviews to collect demographic characteristics, medical records of coronavirus disease 2019, breastfeeding data, and early childhood development was assessed by the Age & Stage Questionnaire (ASQ-3) and Age & Stage Questionnaire Social-emotional (ASQ:SE-2) Chinese versions at three months after childbirth. We used multivariable Poisson regression models to estimate the relative risk (RR) of SARS-CoV-2 infection. Multivariable linear regression models and a mediation model were used to test the direct and indirect associations between SARS-CoV-2 infection and the ASQ-3 score. This study was approved by the Peking University Third Hospital Medical Science Research Ethics Committee (No. IRB00006761-M2020127). Results: In the infection cohort, 13.6% of the children showed social-emotional developmental delay and 13.5% showed overall developmental delay. The corresponding rates in the non-infection cohort were 23.4% and 8.1%. Compared with the non-infection cohort, SARS-CoV-2 infection during pregnancy did not increase the risk of social-emotional (RR = 0.87, 95%CI: 0.51-1.49) or overall (RR = 1.02, 95%CI: 0.60-1.73) developmental delay. The mediation model showed that SARS-CoV-2 infection indirectly affected the ASQ-3 score by increasing the length of mother-infant separation. Conclusions: SARS-CoV-2 during late pregnancy did not increase the risk of developmental delay of offspring three months after delivery. However, SARS-CoV-2 may have indirect effects on early childhood development by increasing mother-infant separation.